Scrutinizing the Bachelor Level Students’ Understanding of Forgiveness - Sharma, Lok Raj; Aryal, Umesh; Koirala, Rabin; Sanjel, Govind Prasad; Upreti, Uttam Prasad (Nepal Journal of Multidisciplinary Research, 2023)
Forgiveness, defined as a deliberate and voluntary act to release oneself from resentment, grievances and the urge for revenge, plays a prominent role in promoting compassion, harmony, and peace. Despite its profound prominence, different people retain a different understanding of its existence. The key objective of this article is to scrutinize the understanding of forgiveness among the bachelor level students enrolled in the faculties of Education and Management at Makawanpur Multiple Campus in Hetauda, Nepal during the academic year 2022-2023. Employing a cross-sectional survey research design, 329 students were randomly gleaned from a pool of 2240 by maintaining a confidence level of 95% and a margin of error of 5%. The respondents were selected using computer-generated random numbers. Primary data were collected through close-ended questions regarding the students' understanding of forgiveness, while secondary data were compiled from extensive reviews of books, journal articles, and website documents spanning the years 1978 to 2013. The findings based on frequency and percent statistics reveal that 170 students (51.7%) perceived forgiveness as a strength, whereas 159 students (48.3%) regarded it as a weakness. Chi-square test shows that there was no significant association between gender and the students’ understanding of forgiveness (χ² = 1.6, df=1, p > .05), whereas there was a significant association between faculty and the students’ understanding of forgiveness (χ² = 55.755, df= 1, p < .05). The practical implication of this article lies in underscoring the need for targeted educational interventions and curriculum enhancements aimed at promoting a deeper comprehension of forgiveness among students for enhancing human relationships and reducing negative emotions.